Type 1 Diabetes and youth sports in Sweden: A field experiment on discrimination - Ali M. Ahmed; Mats Hammarstedt (Research Institute of Industrial Economics (IFN), 2023)
This study evaluated discrimination against children with Type 1 Diabetes Mellitus (T1DM) in Swedish sports clubs through a field experiment. Two fictitious fathers sent emails to 193 top-division clubs in football, floorball, ice hockey, and handball, one disclosing his son's T1DM condition. The investigation focused on disparities in clubs' responses and information provided. Results indicated no significant difference in positive or comprehensive responses between emails mentioning T1DM and those that did not, suggesting minimal bias at initial contact and an inclusive approach by the clubs towards children with T1DM.
Keywords: J14; J71; 330; Type 1 Diabetes Mellitus; Discrimination; Sports clubs; Field experiment